Patients at the centre of care: debriefing patients after caesarean section. Issue 4 (17th October 2019) - Dougan, Claire; Smith, Emma; Ploski, Jennifer; Mc Nally, Arthur; Johnston, Katie
Abstract : Empowering patients and working collaboratively to improve healthcare is a focus for current healthcare development strategies. In obstetric practice, working in collaboration with women to discuss mode of delivery after caesarean section has been shown to impact women's choice. A preliminary survey in our tertiary maternity unit showed 20% of women gained 'full clarity' with the information they received after caesarean-section regarding indication, complications and impact on future delivery. Focus groups identified what information patients required about their surgery. General practitioners (GP) highlighted a lack of communication between secondary and primary care. Junior obstetricians surveyed felt uncertain about debriefing. The aim was to improve monthly 'full clarity' scores to 30% in 6 months. Our team introduced a debrief form, filled by the operator and kept in maternity notes. The operator verbally debriefed as part of their current standard practice. Junior doctors postoperatively debriefed the patient using the form. The triplicate form ensured both patients and primary care received a copy. It was anticipated that in the long term, this would provide consistent information and aid informed decision making in subsequent pregnancies. Review of the forms' use was undertaken weekly. Multidisciplinary input identified barriers to uptake. Plan, Do, Study, Act cycles promoted the project, disseminated results, evidenced growing participation and rewarded consistent form use. Patient groups critiqued the form layout. Teaching aimed to improve junior doctor confidence in debriefing discussions. Sustained participation resulted in effective form uptake. Patient 'full clarity' scores improved to 60% with minimal impact on workload. Teaching successfully improved junior doctor confidence as evidenced by increased documented debrief discussions. GP focus groups felt empowered to counsel women consistently about their surgery increasing clarity for everyone. This project highlights that patient satisfaction improves when we listen to their views and commit to change.